The past and future of knowledge-based growth - Holger Strulik; Klaus Prettner; Alexia Prskawetz (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2012)
Conventional R&D-based growth theory argues that productivity growth is driven by population growth but the data suggest that the erstwhile positive correlation between population and productivity turned negative during the 20th century. In order to resolve this problem we integrate R&D-based innovations into a unified growth framework with micro-founded fertility and schooling behavior. The model explains the historical emergence of R&D-based growth and the subsequent emergence of mass education and the demographic transition. The ongoing child quality-quantity trade-off during the transition explains why in modern economies high growth of productivity and income is associated with low or negative population growth. Because growth in modern economies is based on the education of the workforce, the medium-run prospects for future economic growth - when fertility is going to be below replacement level in virtually all developed countries - are much better than suggested by conventional R&D-based growth theories.
Keywords: J13; J24; O10; O30; O40; 330; R&D; declining population; fertility; schooling; human capital.; Wirtschaftswachstum; Forschung; Bevölkerungsökonomie; Alternde Bevölkerung; Produktivität; Bildungswesen; Humankapital; Wirtschaftsgeschichte; Neue Wachstumstheorie; Theorie; Industriestaaten